Deteksi dan Identifikasi Pelaku Kecurangan Skema Pembagian Rahasia Linear Berbasis Skema Shamir - Zulkaidah Nur Ahzan; Sugi Guritman; Bib Paruhum Silalahi (Jurnal Karya Pendidikan Matematika, 2020)
The method that can be used to maintain security of secret in the form of cryptographic keys is by using secret sharing scheme (SSS). This method is first proposed by Adi Shamir in 1979, where the proposed scheme is a (k, n) threshold scheme. Shamir scheme is a perfect scheme under the assumption that all shareholders present their original share. However, if there are dishonest shareholders who present faked shares then the honest shareholders get nothing but a faked secret. Secret sharing scheme based on linear scheme is a scheme that can detect and identify cheaters who submit faked shares at the secret reconstruction. Detectability of this scheme when  and identifiability when  under the assumption that all shareholders present their shares randomly. After conducting a security analysis of the proposed scheme, it is obtained that to succeed in attack with cheaters who work together to fool honest shareholders then a new polynomial g(x) such that g(1) = , g(2) = , …, g(k - 1) =  and a new detector that has the same value as detector d are needed.